Properties of Bio-Boards Produced from the Mixture of Gigantochloa scortechinii and Themeda arguens as an Alternative to Future Timber - Wahab, Razak; Kamarulzaman, Rashidah; Sulaiman, Mohamad Saiful; Samsi, Hashim W.; Razali, Sofiyah Mohd; Edin, Taharah; Mokhtar , Nasihah; Razak , Muhammad Haziq (Current Overview on Science and Technology Research Vol. 10, 2022)
The materials from the non-wood forest resources as well as the agricultural resources can be as an alternative raw material for timber industry. Thus, the characterizations of composite boards made from two grass family of Gigantochloa scortechinii and Themeda arguens were investigated to develop an eco-friendly bio-composite board. The two species were harvested at their respective matured ages. They were segregated, cut and chipped into smaller pieces, and mixed at five different ratios. They were later mixed thoroughly and bonded together using 12 % and 14 % Urea-formaldehyde (UF) and hot pressed into composite boards. Hardener and wax were added at 1% and 3% weights, respectively, during the mixing process. European standards procedures were followed in the board’s preparation and testing. The boards were tested for physical, mechanical and thermal characterizations by using thermogravimetric analysis. The GT composite boards made from 100% G. gigantochloa, and boards at ratio 30:70 (G. scortechini and T. arguens) produced the best characterization in terms of the values in the physical, mechanical and thermal characteristics. The findings suggest that ratios and resin contents influence the GT composites board properties.